2019
DOI: 10.1080/14789450.2019.1645602
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible oxidative post-translational modifications in heart disease

Abstract: Introduction: Development of specific biomarkers aiding early diagnosis of heart failure is an ongoing challenge. Biomarkers commonly used in clinical routine usually act as readouts of an already existing acute condition rather than disease initiation. Functional decline of cardiac muscle is greatly aggravated by increased oxidative stress and damage of proteins. Oxidative post-translational modifications occur already at early stages of tissue damage and are thus regarded as potential up-coming disease marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 130 publications
(158 reference statements)
0
19
0
Order By: Relevance
“…Given the importance of O/N stresses and associated modifications in the onset and progression of many diseases, redox PTMs, especially irreversible redox PTMs, have been proposed as potential circulating biomarkers for a range of conditions including cardiovascular and pulmonary diseases (Di Domenico et al, 2011 ; Butterfield et al, 2014 ; Frijhoff et al, 2015 ; Mnatsakanyan et al, 2018 ; Tomin et al, 2019 ). Several studies have explored the proteins modified by irreversible redox PTMs (e.g., carbonylation) in cerebrospinal fluid and blood of AD and control patients and have detected differences in oxidation levels of a small number of proteins (Choi et al, 2002 ; Korolainen et al, 2007 ; Korolainen and Pirttilä, 2009 ; Cocciolo et al, 2012 ) suggesting that specific redox-modified proteins could be used as biomarkers for neurodegenerative conditions.…”
Section: The Therapeutic Potential Of Redox Ptms Of Proteinsmentioning
confidence: 99%
“…Given the importance of O/N stresses and associated modifications in the onset and progression of many diseases, redox PTMs, especially irreversible redox PTMs, have been proposed as potential circulating biomarkers for a range of conditions including cardiovascular and pulmonary diseases (Di Domenico et al, 2011 ; Butterfield et al, 2014 ; Frijhoff et al, 2015 ; Mnatsakanyan et al, 2018 ; Tomin et al, 2019 ). Several studies have explored the proteins modified by irreversible redox PTMs (e.g., carbonylation) in cerebrospinal fluid and blood of AD and control patients and have detected differences in oxidation levels of a small number of proteins (Choi et al, 2002 ; Korolainen et al, 2007 ; Korolainen and Pirttilä, 2009 ; Cocciolo et al, 2012 ) suggesting that specific redox-modified proteins could be used as biomarkers for neurodegenerative conditions.…”
Section: The Therapeutic Potential Of Redox Ptms Of Proteinsmentioning
confidence: 99%
“…Next, we investigated in depth the redox state of the proteome of the failing hearts by analysing the oxidative state of cysteines residues, one of the main oxidative signaling mediators that are often modified (oxidized) upon reaction with RNOS [ 13 , 21 ]. To that end, we labeled reduced cysteines (Cys red ) with a “light” N-ethylmaleimide (NEM; L), and subsequently reduced all oxidized cysteines (Cys ox ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to glycolytic enzymes, failing hearts also displayed higher oxidation of cysteine residues of several constituents of the contractile machinery, including titin, a giant scaffold protein which acts as a molecular spring and represents a central node of mechanic signaling [ 49 ]. Oxidation of critical myofilament proteins has been recognized as one of the causes leading to contractile dysfunction under oxidative stress [ 13 , 50 , 51 ]. In particular, higher oxidation of titin in failing hearts is in agreement with previous reports suggesting that oxidation of titin through the formation of disulfide bonds contributes to increased passive stiffness in failing hearts [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, modulating conjunctival wound healing has the potential to improve outcomes after GFS. Recent studies have aroused concern about the role of reactive oxygen species (ROS) and oxidant-antioxidant balance in modulating TGF-βs-induced fibrosis and indicate that increased oxidative stress is critical for the development of fibrotic diseases [10,[27][28][29][30][31]. Some researchers have also shown that the intraocular oxidant-antioxidant balance is altered after GFS and damage/oxidative stress to the trabecular meshwork increases risk of glaucoma [28,32].…”
Section: Introductionmentioning
confidence: 99%